Latinos Shifting Republican?: Evangelical, Pentecostal, and Catholic Charismatic Voting in the 2020 Election in the U.S., Florida and Texas - Espinosa, Gastón (Pneuma, 2022)
This article utilizes the Latino Religions and Politics National Survey (n = 1,292) to provide a preliminary investigation into Latino religious and political identity and voting results in the 2020 Election. It provides important new data on the Latino vote lean by religion (Catholic, Protestant, Evangelical, Pentecostal, Catholic Charismatic), with special attention to the critical role that religion in general and Evangelicals and Pentecostals/Charismatics in particular may have played in helping to increase Latino Republican support for President Trump across the nation from 28 percent in 2016 to 32 percent in 2020 and increase his levels of support in Florida and Texas. While religion is just one of many important variables and factors that may help explain the recent if subtle Latino shift towards the Republican Party, it is nonetheless important.